ADHD-related attentional variability and its impact on postural stability in young adults - Yazici-Mutlu, Çiğdem; Seçinti, Can; Ahmetoğlu, Aber (Frontiers in Human Neuroscience, 2026)
PurposePostural control is influenced by attentional demands, yet the role of attention-related individual differences in young adults remains underexplored. This study examined whether sustained attention performance is associated with postural stability in individuals with and without potential ADHD traits (pADHDt)-related attentional variability.MethodsForty-two adults (18–35 years) were grouped based on ASRS scores into a pADHDt group (ASRS > 14; n = 21) and a comparison group (ASRS < 14; n = 21). Sustained attention was assessed using the Sustained Attention to Response Task (SART). Postural stability was measured with the ProKin 252 stabilometer across three stance conditions (two-foot, tandem, soft surface), with and without a verbal cognitive task (backward counting), under eyes-open and eyes-closed conditions. Center of pressure (CoP) sway area and medial–lateral (ML) and anterior–posterior (AP) sway velocities were analyzed using mixed-design ANOVA with Bonferroni correction.ResultsParticipants in the pADHDt group made more SART errors and showed slower reaction times than those in the comparison group (p < 0.05). During cognitively demanding standing tasks, the pADHDt group exhibited larger CoP sway areas in two-foot and tandem stances with eyes open, and in tandem stance with eyes closed (p < 0.05). No group differences were observed in ML or AP sway velocities.ConclusionAdults with ADHD-related attentional variability exhibit differences postural stability under increased cognitive demands, suggesting a role of attentional control in balance-related motor behavior in young adults with pADHDt.